Police and youth - Penn, Everette B. (Routlege series on practical and evidence based policing, 2022)
"This book brings the knowledge gained from the Teen And Police Service Academy (TAPS), which has been implemented internationally to create partnerships with at-risk teens and police, proactively addressing some of the most pressing conditions in their communities. Readers will learn about the nuances of both youth culture and police culture and will better understand the conflict stemming from race and social class. Straightforward solutions stemming from the President's Task Force on 21st Century Policing are demonstrated to provide useful strategies for communities struggling with police-youth relations. This book is especially germane to Texas schools and law enforcement, which are to comply with Community Safety Education Act of Texas. It mandates instruction for all peace officers, high school seniors, those applying for their driver's license and those required to take corrective driver instruction. Police and YOUth is ideal as a primer for students, instructors, police officers, and citizens who stand to benefit from improving police-youth relations. It provides the tools needed to educate all parties and ultimately improve relations between police and the communities they serve"--